Bad Blood / [book 4] - Barnes, Jennifer Lynn, 1983- (Quercus, 2024)
When Cassie Hobbes joined the FBI’s Naturals program, she had one goal: uncover the truth about her mother’s murder. But now, everything Cassie thought she knew about what happened that night has been called into question. Her mother is alive, and the people holding her captive are more powerfuland dangerousthan anything the Naturals have faced so far. As Cassie and the team work to uncover the secrets of a group that has been killing in secret for generations, they find themselves racing a ticking clock. The bodies begin piling up, the deaths hit closer and closer to home, and it soon becomes apparent that this time, the Naturals aren’t just hunting serial killers. They’re being hunted themselves.